MISSION AS INCULTURATION - Manikkam, Thomas (Journal of Dharma, 1981)
Mission, understood as the transmission of an authentic message for the experiential realization of a people to whom it is addressed, requires an integral method for effective communication. This method is called Inculturation. Message is of some person to some other person or persons who belong to a completely different context. In order that the message be received properly and perfectly to the effect of translating it into constructive action the communication should be done in such a way as to motivate the genius of people for creating, thinking and responsible actions. This implies that the message itself should be worded in the intelligibility and language of the addressee; and the bearer should take into account the feelings, imagination, sensitivity, and thought pattern of the people to whom he is bearing that message. To put this in the language of culture, it is called the process of inculturation. Mission implies an Inculturation process, without which it would be like talking in the wilderness.